2015
DOI: 10.1088/1674-4527/15/8/013
|View full text |Cite
|
Sign up to set email alerts
|

CaII H&K emission distribution of ∼ 120 000 F, G and K stars in LAMOST DR1

Abstract: We present chromospheric activity index S HK measurements for 119 995 F, G and K stars with high signal-to-noise ratio (S/N > 80) spectra, extracted from LAMOST DR1 in SDSS g band. The index δS for each of these stars is calculated by the difference between its S HK value and the baseline determined from very inactive stars. The effect of metallicity on measurement of δS varies with stellar T eff . No evident Vaughan-Preston gap appears in our sample. The relation between δS and vertical distance from the Gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
125
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 48 publications
2
125
1
Order By: Relevance
“…Despite being very water soluble, the SS peptides are remarkably cell permeable, and they are readily taken up and act on all cell types, including endothelial cells, renal and intestinal epithelial cells, myotubes, cardiomyocytes, macrophages and neurons (Zhao et al, 2003;Cho et al, 2007b;Han et al, 2009;Zhu et al, 2010;Andersson et al, 2011;Calkins et al, 2011;Li et al, 2011;Dai et al, 2011a;Gilliam et al, 2012;Kloner et al, 2012;Birk et al, 2013b). The mechanism of cellular uptake for these polar peptides is consistent with diffusion as their uptake is linear and independent of receptor-or transporter-mediated processes (Zhao et al, 2003). Confocal microscopy with fluorescent-labelled analogues suggested that these compounds are localized to mito-chondria (Zhao et al, 2004).…”
Section: Discovery Of a New Class Of Small Molecules That Target Cardmentioning
confidence: 99%
“…Despite being very water soluble, the SS peptides are remarkably cell permeable, and they are readily taken up and act on all cell types, including endothelial cells, renal and intestinal epithelial cells, myotubes, cardiomyocytes, macrophages and neurons (Zhao et al, 2003;Cho et al, 2007b;Han et al, 2009;Zhu et al, 2010;Andersson et al, 2011;Calkins et al, 2011;Li et al, 2011;Dai et al, 2011a;Gilliam et al, 2012;Kloner et al, 2012;Birk et al, 2013b). The mechanism of cellular uptake for these polar peptides is consistent with diffusion as their uptake is linear and independent of receptor-or transporter-mediated processes (Zhao et al, 2003). Confocal microscopy with fluorescent-labelled analogues suggested that these compounds are localized to mito-chondria (Zhao et al, 2004).…”
Section: Discovery Of a New Class Of Small Molecules That Target Cardmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Narrowband response organic photodetectors are more challenging to engineer because of the relatively broad photon harvesting range of organic materials, especially for photomultiplication organic photodetectors (PM-OPDs) with EQE larger than 100%. [13][14][15][16] The PM-OPDs can be realized through interfacial trap-induced charge tunneling injection, the spectral response range of PM-OPDs is determined by the trapped-charge-distribution near the opposite charge injection electrode, which provides more possibilities to adjust response range of PM-OPDs. [17][18][19] The PM-OPDs with PFN instead of PEDOT:PSS as anode interfacial layer can work well under forward and reverse bias, exhibiting broadband response from 350 nm to 800 nm and narrowband response peak at 800 nm with full width at half-maximum (FWHM) of 40 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[20], which looked at bulge formation, and in Ref. [21], which considered interesting aspects of the history of the Milky Way-Andromeda binary system in MOND, in contrast with what is expected in the ΛCDM paradigm. Variations of a 0 would even accentuate the differences.Thus, one indirect way to pinpoint variation of a 0 with cosmic time is to study the redshift evolution of galactic structure and dynamics, to see if some of it can be attributed to such variation.…”
mentioning
confidence: 99%
“…[20], which looked at bulge formation, and in Ref. [21], which considered interesting aspects of the history of the Milky Way-Andromeda binary system in MOND, in contrast with what is expected in the ΛCDM paradigm. Variations of a 0 would even accentuate the differences.…”
mentioning
confidence: 99%